The role of science and scientists in a complex and fragile world. Issue 9 (20th October 2016) - Balzani, Vincenzo
Abstract : Complexity is a common feature of all problems facing mankind and in such a complex world we need science to propose solutions. Science, indeed, is growing in all directions and permeates more and more the human society. As pointed out by several scientists, however, the development of science increases the fragility of our world. A democratic society must discuss the role of science and must collectively take decisions on the development of science. Scientists should be concerned about the world in which we live and the society that we are going to construct. They should discuss the relationship between science and society with students, explain science to laymen, and educate politicians on the most important scientific issues, thereby playing an important role as authoritative, informed, and concerned citizens of the planet Earth.